2017
DOI: 10.15587/1729-4061.2017.108876
|View full text |Cite
|
Sign up to set email alerts
|

Changing the quality of ground meat for sausage products in the process of grinding

Abstract: Type of grinding Average size of a piece (particle), mm before grinding after grinding Coarse up to 300 up to 100 Medium up to 200 60...10 Fine 200.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…One of the advantages of the first direction may be a higher growth rate of planting material in reservoirs (compared to ponds). This allows forming a more resistance to the conditions of a particular reservoir initial herd of aquaculture facilities (Raoult, Gaston, and Taylor, 2018; Buzevych and Buzevych, 2017; Khrystenko et al, 2012;Sukhenko et al, 2017;Zakharchenko et al, 2019;Didenko, 2007). To verify this factor, we conducted a comparative analysis of the rates of linear and weight growth of annuals and biennials of hybrids of silver and bighead carp grown in pond conditions and young-of-the-year -triennials in the reservoir.…”
Section: Resultsmentioning
confidence: 99%
“…One of the advantages of the first direction may be a higher growth rate of planting material in reservoirs (compared to ponds). This allows forming a more resistance to the conditions of a particular reservoir initial herd of aquaculture facilities (Raoult, Gaston, and Taylor, 2018; Buzevych and Buzevych, 2017; Khrystenko et al, 2012;Sukhenko et al, 2017;Zakharchenko et al, 2019;Didenko, 2007). To verify this factor, we conducted a comparative analysis of the rates of linear and weight growth of annuals and biennials of hybrids of silver and bighead carp grown in pond conditions and young-of-the-year -triennials in the reservoir.…”
Section: Resultsmentioning
confidence: 99%
“…Providing the population with high-quality food products of increased nutritional and biological value is an urgent issue of today, due to a violation of the nutritional status, and a lack of several essential nutritional factors. In this regard, the concept of creating new food products, chemically balanced, enriched with functional components, and ensuring their immutability, health safety after technological processing, as well as during storage, is becoming increasingly important (Sukhenko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of literature sources has shown that the most effective way to achieve goals is to select the appropriate feed and feeding strategy. The consumption of a part of the feed for energy needs is often variable and requires a detailed study, taking into account all the features of the study object (Buchtová and Ježek, 2011;Sukhenko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%